A Review of the Emotional Aspects of Neuropathic Pain: From Comorbidity to Co-Pathogenesis. Issue 1 (December 2017) - Torta, Riccardo; Ieraci, Valentina; Zizzi, Francesca
Abstract Neuropathic pain is characterized by both sensory and affective disturbances, supporting the notion that pain and mood disorders share common pathogenetic mechanisms. Moreover, biological and neuroimaging data show that common brain areas are involved in the modulation of painful and emotional experiences. Improved understanding of the molecular mechanisms underlying the role of neuroinflammation in regulation of affective behavior in neuropathic pain states is important for the development of novel therapeutic strategies. Psychological issues must be considered a factor influencing treatment and outcome in patients with neuropathic pain. Funding: Pfizer, Italy.